Augmentation in seed germination through pre-treatments in sea buckthorn (Hippophae salicifolia D. Don): An important multipurpose shrub of himalaya - Yadav, Patade Vikas; Kumar, Kundan; Gupta, Anand Kumar; Grover, Atul; Negi, Prem Singh; Dwivedi, Sanjay Kumar (Indian Forester, 2020)
No abstract